Multiplicity of Infection and Disease Severity in Plasmodium vivax - Pacheco, M. Andreína; Lopez-Perez, Mary; Vallejo, Andrés F.; Herrera, Sócrates; Arévalo-Herrera, Myriam; Escalante, Ananias A. (PLoS neglected tropical diseases, 2016)
Multiplicity of infection (MOI) refers to the average number of distinct parasite genotypes concurrently infecting a patient. Although several studies have reported on MOI and the frequency of multiclonal infections in Plasmodium falciparum, there is limited data on Plasmodium vivax. Here, MOI and the frequency of multiclonal infections were studied in areas from South America where P. vivax and P. falciparum can be compared. As part of a passive surveillance study, 1,328 positive malaria patients were recruited between 2011 and 2013 in low transmission areas from Colombia. Of those, there were only 38 P. vivax and 24 P. falciparum clinically complicated cases scattered throughout the time of the study. Samples from uncomplicated cases were matched in time and location with the complicated cases in order to compare the circulating genotypes for these two categories. A total of 92 P. vivax and 57 P. falciparum uncomplicated cases were randomly subsampled. All samples were genotyped by using neutral microsatellites. Plasmodium vivax showed more multiclonal infections (47.7%) than P. falciparum (14.8%). Population genetics and haplotype network analyses did not detect differences in the circulating genotypes between complicated and uncomplicated cases in each parasite. However, a Fisher exact test yielded a significant association between having multiclonal P. vivax infections and complicated malaria. No association was found for P. falciparum infections. The association between multiclonal infections and disease severity in P. vivax is consistent with previous observations made in rodent malaria. The contrasting pattern between P. vivax and P. falciparum could be explained, at least in part, by the fact that P. vivax infections have lineages that were more distantly related among them than in the case of the P. falciparum multiclonal infections. Future research should address the possible role that acquired immunity and exposure may have on multiclonal infections and their association with disease severity.